Active Methodologies and Innovation in Teaching Portuguese Phonetics as a Foreign Language (Revista Lusófona de Educação, 2025)
This study, carried out at the University of Seville (Spain), during the academic year 2022/2023, aimed to investigate the effectiveness of active methodologies in the teaching of Portuguese phonetics as a foreign language. Configured as exploratory research, the study aims to analyse the applicability and results of this specific approach in the university context. The sample consisted of 46 students of different nationalities, aged between 19 and 50, distributed at different levels of proficiency in Portuguese, covering levels A2 and B1. The methodology employed consisted of interactive and practical activities, including pronunciation games, sound identification exercises and guided repetition practice. In addition, collaborative learning techniques and audio-visual resources were used to facilitate the process of phonetic acquisition. The results of the research revealed a significant improvement in the participants’ ability to identify and reproduce specific phonetic sounds of Portuguese, demonstrating an increase in listening comprehension and correct pronunciation by the learners.